The place of pemetrexed in the management of non-small-cell lung cancer patients. Issue 3 (March 2013) - Tomasini, Pascale; Greillier, Laurent; Khobta, Nataliya; Barlesi, Fabrice
Non-small cell lung cancer (NSCLC) remains the leading cause of cancer death worldwide. Chemotherapy is included in the management of the majority of NSCLC patients either in addition to a local treatment (surgery/radiotherapy) or alone. In this setting, pemetrexed has become one of the most important partners of current chemotherapy regimens for nonsquamous NSCLC patients. Indeed, pemetrexed demonstrated a comparable efficacy to other previously available drugs in NSCLC, with however a better safety profile and an easier schedule of administration. In addition, pemetrexed demonstrated a greater efficacy in nonsquamous NSCLC that lead to an exploration of the underlying potential biological background. It is now suggested that the tumor thymidylate synthase level may act as a predictor of pemetrexed efficacy, therefore potentially providing clinicians in the future with a predictor of efficacy, which it is usually lacking with standard chemotherapies.